Validation of patient- and GP-reported core sets of quality indicators for older adults with multimorbidity in primary care: results of the cross-sectional observational MULTIqual validation study - Schäfer, Ingmar; Schulze, Josefine; Glassen, Katharina; Breckner, Amanda; Hansen, Heike; Rakebrandt, Anja; Berg, Jessica; Blozik, Eva; Szecsenyi, Joachim; Lühmann, Dagmar; Scherer, Martin (BMC medicine, 2023)
Background: Older adults with multimorbidity represent a growing segment of the population. Metrics to assess quality, safety and effectiveness of care can support policy makers and healthcare providers in addressing patient needs. However, there is a lack of valid measures of quality of care for this population. In the MULTIqual project, 24 general practitioner (GP)-reported and 14 patient-reported quality indicators for the healthcare of older adults with multimorbidity were developed in Germany in a systematic approach. This study aimed to select, validate and pilot core sets of these indicators. Methods: In a cross-sectional observational study, we collected data in general practices (n = 35) and patients aged 65 years and older with three or more chronic conditions (n = 346). One-dimensional core sets for both perspectives were selected by stepwise backward selection based on corrected item-total correlations. We established structural validity, discriminative capacity, feasibility and patient-professional agreement for the selected indicators. Multilevel multivariable linear regression models adjusted for random effects at practice level were calculated to examine construct validity. Results: Twelve GP-reported and seven patient-reported indicators were selected, with item-total correlations ranging from 0.332 to 0.576. Fulfilment rates ranged from 24.6 to 89.0%. Between 0 and 12.7% of the values were missing. Seventeen indicators had agreement rates between patients and professionals of 24.1% to 75.9% and one had 90.7% positive and 5.1% negative agreement. Patients who were born abroad (− 1.04, 95% CI =  − 2.00/ − 0.08, p = 0.033) and had higher health-related quality of life (− 1.37, 95% CI =  − 2.39/ − 0.36, p = 0.008), fewer contacts with their GP (0.14, 95% CI = 0.04/0.23, p = 0.007) and lower willingness to use their GPs as coordinators of their care (0.13, 95% CI = 0.06/0.20, p < 0.001) were more likely to have lower GP-reported healthcare quality scores. Patients who had fewer GP contacts (0.12, 95% CI = 0.04/0.20, p = 0.002) and were less willing to use their GP to coordinate their care (0.16, 95% CI = 0.10/0.21, p < 0.001) were more likely to have lower patient-reported healthcare quality scores. Conclusions: The quality indicator core sets are the first brief measurement tools specifically designed to assess quality of care for patients with multimorbidity. The indicators can facilitate implementation of treatment standards and offer viable alternatives to the current practice of combining disease-related metrics with poor applicability to patients with multimorbidity.
Gesehen am 13.06.2023